Myocardial adaptation in different endurance sports: an echocardiographic study - Hoogsteen, J.; Hoogeveen, A.; Schaffers, H.; Wijn, P. F.; van Hemel, N. M.; van der Wall, E. E. (The International Journal of Cardiovascular Imaging, 2004)
Of this study was to investigate three groups of highly trained competitive endurance athletes consisting of marathon runners, triathletes and cyclists for differences in left ventricular adaptation. METHODS: 25 marathon athletes, 21 triathlon athletes and 38 cyclists underwent a standard echocardiographic and Doppler study. RESULTS: The left ventricular internal diameter in diastole divided by body surface area was significantly larger in cyclists than in marathon runners (31.6+/-3.0 vs. 30.0+/-2.0 mm/ m2, p < 0.05) but did not differ of that of triathletes. Left ventricular mass was significantly different between marathon runners and triathletes (253.6+/-63.7 vs. 322.0+/-62.1 g, p < 0.005) and between marathon runners and cyclists (253.6+/-63.7 vs. 314.2+/-79.2 g, p < 0.005). Systolic wall stress was significantly different between the marathon runners and the triathletes (88.4+/-11.7 vs. 78.9+/-11.0 g/cm2 p < 0.05). Only a minority of the endurance athletes showed concentric remodeling (7%), whereas a majority showed eccentric remodeling (65%) of the left ventricle. The prevalence of eccentric remodeling was more apparent in cyclists. There were some specific differences in left ventricular diastolic function between the three different endurance sports, but no left ventricular diastolic dysfunction could be detected. CONCLUSION: There is a sport-specific left ventricular adaptation in endurance athletes. The triathlon heart and the heart of a cyclist differ significantly from a marathon heart.